2022
DOI: 10.1021/jacs.2c09262
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Amyloid Polymers Exploit Dynamic Covalent Linkage to Temporally Control Charge-Selective Catalysis

Abstract: Extant proteins exploit thermodynamically activated negatively charged coenzymes and hydrotropes to temporally access mechanistically important conformations that regulate vital biological functions, from metabolic reactions to expression modulation. Herein, we show that a short amyloid peptide can bind to a small molecular coenzyme by exploiting reversible covalent linkage to polymerize and access catalytically proficient nonequilibrium amyloid microphases. Subsequent hydrolysis of the activated coenzyme lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…These systems have designed and developed judiciously by selecting the basic amino acids and Nap-F at various combinations as phenylalanine 4,20 is well known for its assembly propensity and basic amino acids are well known for their esterase-like activity in various peptides and proteins. 32,33 , 38,39 No catalytic activity has been identified from the native hydrogel ( Nap-F ) nor its diluted self-assembled solution. However, the negligible effect of phosphate anion in the phosphate buffer used for the preparation of the Nap-F -hydrogel has been noted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems have designed and developed judiciously by selecting the basic amino acids and Nap-F at various combinations as phenylalanine 4,20 is well known for its assembly propensity and basic amino acids are well known for their esterase-like activity in various peptides and proteins. 32,33 , 38,39 No catalytic activity has been identified from the native hydrogel ( Nap-F ) nor its diluted self-assembled solution. However, the negligible effect of phosphate anion in the phosphate buffer used for the preparation of the Nap-F -hydrogel has been noted.…”
Section: Resultsmentioning
confidence: 99%
“…31 Das and his co-workers discovered imidazole-conjugated heptapeptides (a general peptide sequence Im–XLVFFALNH 2 where, Im = imidazole, X = lysine ( K )/arginine ( R )/ornithine (O)/glutamic acid (E), V = valine, F = phenylalanine, A = alanine and L = leucine); for ester hydrolysis reaction where imidazole and lysine-containing peptide nanotubes as well as co-assembled Im–KLVFFAL–NH 2 and (2-(4-formylphenoxy)-2-oxoethanesulfonate) exhibited efficient catalysis. 32,33 Amphiphilic histidine coupled with stearic acid and its nitrophenol ester have been utilized for transient self-assembled cooperative hydrolysis of ester. 34 L H – D F – D F ( l -histidine– d -phenylalanine– d -phenylalanine)-derived hydrogel has been employed previously for the ester hydrolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolytically competent imidazole group was installed next to the lysine residue of KL, generating the sequence Im-KLVFFAL (cat-KL). [28,[42][43][44][45][46] We expected, apart from the leucine rich surface, cat-KL could utilise co-linear arrays of dyads of lysine and imidazole groups, where lysines could offer covalent anchors for enantioselective substrate binding and imidazole moieties could show subsequent hydrolysis. cat-KL formed homogeneous nanotubular morphologies at neutral pH and demonstrated a hydrolytic activity towards (�) 1c, 3b, c and Figures S10-S15).…”
Section: Methodsmentioning
confidence: 99%
“…[ 32 ] Das et al. [ 33 ] showed that a short amyloid peptide could bind to a small molecular coenzyme by exploiting reversible covalent linkage to polymerize and access catalytically proficient nonequilibrium amyloid microphases. Subsequent hydrolysis of the activated coenzyme led to depolymerization, realizing a variance of the surface charge of the assembly as a function of time.…”
Section: Mechanisms and Strategies Of Protein Nanosizingmentioning
confidence: 99%